Causal association between celiac disease and inflammatory bowel disease: A two-sample bidirectional Mendelian randomization study - Yuan, Shuai; Kim, Ji Hun; Xu, Pai; Wang, Zhao (Frontiers in Immunology, 2023)
Background: An epidemiological link between celiac disease (CeD) and inflammatory bowel disease (IBD) has been well established recently. In this study, Mendelian randomization (MR) analysis was performed employing pooled data of publicly available genome-wide association studies (GWAS) to determine the causal relationship between CeD and IBD, encompassing ulcerative colitis (UC) and Crohn's disease (CD). Methods: Dataset of CeD was acquired from GWAS for 12,041 cases and 12,228 controls. A GWAS of more than 86,000 patients and controls was used to identify genetic variations underlying IBD. MR analyses were performed with an inverse-variance-weighted approach, an MR-Egger regression, a weighted-mode approach, a weighted-median method, and sensitivity analyses of MR pleiotropy residual sum and outlie (MR-PRESSO). Results: MR demonstrated that genetic predisposition to CeD was linked to a augmented risk of IBD (OR: 1.1408; 95% CI: 1.0614-1.2261; P = 0.0003). In the analysis of the two IBD subtypes, genetic predisposition to CeD was also linked to increased risks of UC (OR: 1.1646; 95% CI: 1.0614-1.2779; P = 0.0012) and CD (OR: 1.1865; 95% CI: 1.0948-1.2859; P = 3.07E-05). Reverse MR analysis results revealed that genetic susceptibility to IBD and CD was correlated with an augmented risk of CeD. However, there was no genetic correlation between UC and CeD. All of the above results were validated with other GWAS databases. Conclusion: There is a bidirectional causal relationship of CeD with IBD and CD. However, UC only augments the risk of developing CeD.